SOCIALIZING INNOVATIVE TEACHING TO SUPPORT PRIMARY SCHOOL DIGITALIZATION FOR PRIMARY SCHOOL TEACHERS IN JAKARTA PROVINCE IN INDONESIA - Arita Marini; Sri Nuraini; Desy Safitri; Sujarwo; Nurzengky Ibrahim; Yustia Suntari (Bajang Institute, 2022)
International collaboration of community service is in the Province of Jakarta. The target of this community service is elementary school teachers in the Province of Jakarta in Indonesia. The problem with the target audiences is that the competences in applying innovative teaching of elementary school teachers in the Province of Jakarta has not been managed properly and their interests in implementing innovative teaching are still low. The socialization of applying innovative teaching given is related to developing the competences of applying innovative teaching to support primary school digitalization with appropriate learning activity programs, understanding the concepts of innovative teaching, school digitalization, and assessment of the competences of applying innovative teaching to measure the success of this community services. Evaluation of process and results is done to find out the competences of elementary school teachers in applying innovative teaching.